Mutation of Dystopian Identity in the Age of Posthumanism: Literary Speculations - Bezrukov, Andrii; Bohovyk, Oksana (Respectus Philologicus, 2022)
Dystopia, while deconstructing utopian ideas, generates a special type of identity as the consequence of a deviation from anthropocentric principles, crises of national and cultural worldviews, and manifestations of social shifting in a posthumanist world. The article focuses on four symptomatic dystopian texts – George Orwell’s “Nineteen Forty-Eight”, Ray Bradbury’s “Fahrenheit 451”, Ahmed K. Towfik’s “Utopia”, and Salman Rushdie’s “Quichotte” – to explicate the dichotomous nature of the opposition of identity vs society in posthumanist transformations. Those conditions are considered a cause of the mutation of dystopian identity that troubles its anthropological bases and modes of existence. To reconstruct the posthumanist context and its influence on the dystopian identities in the selected novels, this study has exploited a mixture of the following methods: intertextual, cultural, and genre ones; phenomenological approach; hermeneutic interpretation; conceptualisation, etc. The novelty of the study emanates from the very attempt to interpret the writers’ names of the AGEs represented in the books as a background of storytelling and a lens through which the posthumanist space is transformed from a dystopian perspective.
Keywords: shifting identity; quasi-reality; (after)humanism; (post)modernity; dichotomy